Sportswashing or Strategic Branding? The Saudi Pro League's Role in Reshaping Global Perceptions of Saudi Arabia - Imam Ansori; Muhammad Yamin; Arif Darmawan; Soni Martin Anwar (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
This study analyzes the change of the Saudi Pro League (SPL) from 2021 to 2024, assessing whether these initiatives represent sportswashing or authentic nation branding. Since 2021, Saudi Arabia has allocated billions into the acquisition of international football talents and the enhancement of facilities, notwithstanding global condemnation of its human rights record. This research utilizes Anholt's nation branding hexagon framework and adopts a qualitative case study technique with comparative aspects, incorporating official documents, public opinion surveys, media content analysis, and tourism statistics. Findings indicate a multifaceted "strategic sports diplomacy" approach that surpasses the simplistic sportswashing/branding dichotomy, yielding disproportionate outcomes across several objectives. Despite SPL's notable commercial success, including airing in over 130 countries, generating over $300 million in annual revenue, and attracting an additional 310,000 tourists, enhancements in reputation within Western markets were limited, especially among viewers emphasizing human rights issues. The study demonstrates a "Western perception paradox," wherein substantial visibility gains did not result in enhanced favorability, while demographic analysis indicates markedly more positive perceptions among younger viewers, active fans, and non-Western demographics. This study enhances the theoretical comprehension of sports diplomacy by illustrating how audience segmentation influences effectiveness across demographic, geographic, and cultural dimensions, thereby contesting simplistic assessments of sports-based nation branding and offering frameworks for analyzing the multifaceted outcomes of modern sports diplomacy.